Ai-enhanced reliability centered maintenance for high voltage gas circuit breakers - Payam Hedayatnia; Mohammad Hamed Samimi; Milad Mohammadhosein; Kaveh Niayesh (International Journal of Electrical Power & Energy Systems, 2025)
Circuit breakers (CBs) are critical for protection and switching in power systems, requiring effective maintenance strategies to ensure reliability and longevity. Traditional approaches, including time-based, preventive, and condition-based maintenance (CBM), can be costly and inefficient. Reliability-centered maintenance (RCM) offers a more strategic alternative by prioritizing maintenance based on equipment condition and system importance. This paper presents a novel AI-driven method for assessing the condition of high-voltage circuit breakers (HVCBs) and optimizing maintenance schedules, with a particular focus on contact erosion. The proposed framework comprises three stages, each incorporating progressively more data to enhance assessment accuracy. The methodology is validated in a real-world network, comparing CBM and RCM strategies. Results indicate that integrating AI with RCM improves maintenance planning, reduces costs, and enhances system reliability. This approach provides a cost-effective and data-driven solution for CB maintenance in power systems.